RANCANGAN PERALATAN ALTERNATOR PADA SISTEM PENGAPIAN BUSI ELEKTRONIK CDI SEPEDA MOTOR - Marpaung, Parlindungan Pandapotan (Pusat Riset dan Inovasi Nasional, 2022)
In automotive spark plug ignition, gasoline-fueled vehicles require spark ignition system equipment. One of the electronic cdi spark plug ignition systems uses electronic equipment and components that replace conventional spark plug ignition systems. In this study, the design of the electronic cdi spark plug ignition system using the main equipment of the alternator produces an ac output voltage source on the exiter coil winding. The results of the design of the equipment are generated by a timer signal from the pulser component related to the rpm speed of the alternator permanent magnet rotor shaft which is driven by the rotation of the ac electric motor shaft. The ignition timing process of the spark plug is controlled by the charge/discharge condition of the electronic capacitor charge in the cdi device to produce an ac power supply voltage, the output time function to the primary input of the coil is expressed as the Vprimer(t) parameter in volts. The result of the primary voltage Vprimer(t) at the primary input of the induced coil generates a high voltage at the secondary output of the ignition coil, which is expressed as the Vo(coil) parameter. The result of a high voltage Vo(coil) momentarily connected to the spark plug produces spark ignition which indicates that there is a spark in the spark plug gap.